Nasolabial Cyst: A Sporadic Disease Entity (Global Journal of Medical Research, 2020)
Abstract not found
Keywords: nasolabial; nasoalveolar; cyst; FNAC (fine needle aspiration cytology); OPG (orthopantomogram)